An E2F5-TFDP1-BRG1 Complex Mediates Transcriptional Activation of MYCN in Hepatocytes - Fan, Zhiwen; Kong, Ming; Miao, Xiulian; Guo, Yan; Ren, Haozhen; Wang, Jinglin; Wang, Shuai; Tang, Ning; Shang, Longcheng; Zhu, Zhengyi; Liu, Hanyi; Zhu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Liver regeneration is characterized by cell cycle reentrance of hepatocytes. N-Myc, encoded by MYCN, is a member of the Myc family of transcription factors. Elevation of MYCN expression has been noted in the course of liver regeneration whereas the underlying mechanism remains unclear. Here we describe that up-regulation of MYCN expression, as measured by quantitative PCR, Western blotting, and immunohistochemical staining, paralleled liver regeneration in animal and cell models. MYCN expression was up-regulated as a result of transcriptional activation. Ingenuity pathway analysis (IPA) revealed several up-stream transcriptional regulators for MYCN and RNA interference validated E2F5 and TFDP1 as essential for HGF-induced MYCN trans-activation. Further examination showed that deficiency of BRG1, a chromatin remodeling protein, attenuated MYCN induction during liver regeneration. BRG1 interacted with and was recruited by E2F5/TFDP1 to the MYCN promoter. Mechanistically, BRG1 might play a role regulating histone H3 acetylation and H3K4 trimethylation and facilitating/stabilizing the binding of RNA polymerase II surrounding the MYCN promoter. Over-expression of ectopic MYCN in BRG1-null hepatocytes overcame deficiency of proliferation. Importantly, a positive correlation between MYCN expression and BRG1/E2F5/TFDP1 expression was observed in human liver specimens. In conclusion, our data identify a novel epigenetic pathway where an E2F5-TFDP1-BRG1 complex regulates MYCN transcription to promote liver regeneration.